Development of a prunelike candied product from Balimbing (Averrhoa carambola Linn.) - Ortega, Myrna M.; Alabastro, Estrella F. (1975.)
This study was concerned with the development of a dehydrated candied product from balimbing which could approximate the appearance and flavor of prunes. The four phases of the study included the determination of the following: optimum syrup concentration prior to drying, effect of salting on the characteristics of product, best syruping and drying method, and the effect of addition of brown coloring food dye to improve the color of the final product. Subjective tests were done on each phase to evaluate color, flavor, texture and acceptability of the product. The dried sample were analyzed for moisture, pH, soluble solids content, and titratable acidity. From the study, a standardized procedure was developed fro the processing of balimbing into a prunelike candied product. The fruits were soaked in 10% brine prior to syruping in 40°B following the step-up method. Drying was done in the cabinet drier for 8 hours at 120 to 140°F.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Balimbing; Fruit, Candied; Fruit -- Preservation